Hendro Fernando's Communication Patterns in The Deradicalization Programs: A Science Perspective Analysis - Supandi, Asep; Syauqillah, Muhamad (Postgraduate, University of Mataram, 2025)
The communication between ex-militants and non-militants, known as the in-group, is the main key in the deradicalization programs in Indonesia. However, until now, there has been no specific communication pattern applied by ex-militants in the deradicalization process. One of the key factors in the success of the deradicalization programs is when ex-militants are willing to open up and discuss with ex-militants who have pledged their allegiance to the Republic of Indonesia. This study aims to elaborate aspects of communication patterns, especially the communication patterns carried out by Hendro Fernando, a former prisoner, in the deradicalization program. The method used in this research is descriptive qualitative research. The results showed that the communication patterns applied by Hendro Fernando, through storytelling techniques with the story of King Najasi, had significant benefits in helping the prisoners get out of radical ideology and became one of the supporting factors for the success of the deradicalization program.